Semiosis of the Erótic Offers: Female Offers, New Economic Model with Minimum Inclusion: Free Trade Agreements and Strip Industry in Mexico - López Villagrán, Gilberto (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This reflection stems from a series of qualitative investigations related to the profound cultural, aesthetic and erotic impacts on Mexican society. The insertion of Mexico into the Free Trade Agreement, together with the United States and Canada (1994) promoted new erotic offers, as well as the construction of images and narratives of a country that was reinventing itself and becoming Americanized at a dizzying pace. Likewise, social representations and their ideological load are intended to be denaturalized, now that economic exchanges have been renegotiated in a new trade agreement (2018). And a government that symptomatically calls itself Morena and promises a new historical narrative.